DIFFERENCE IN ASSOCIATION OF DEPRESSION WITH IADL DECLINE BETWEEN 70S AND 80S AGE GROUPS. (16th November 2018) - Kiyoshige, E; Kabayama, M; Sugimoto, K; Arai, Y; Ishizaki, T; Gondo, Y; Rakugi, H; Kamide, K
Abstract: Background: Instrumental activities of daily living (IADLs) indicates the independence of community-dwelling elderly. IADL decline was reported to be associated with age and depression. We aimed to investigate whether association of depressive symptoms with IADL decline was modified by age groups (i.e, 70s and 80s), and estimate the effects of depressive symptoms on IADL. Methods: We conducted longitudinal analysis among participants aged 70 and 80 at baseline from Septuagenarians, Octogenarians, Nonagenarians Investigation with Centenarians (SONIC) study. IADL decline was assessed by the differences in scores measured at the baseline and the 3-year follow-up. As a main predictor, depressive symptoms were measured by the Geriatrics Depression Scale (GDS). As possible confounders, we considered cognitive function, body mass index, economic status, medical history of cardiovascular disease, and sex. Using multiple group analysis, we examined differences between the age groups (i.e, 70s and 80s) in the association of depressive symptoms with IADL decline. Results: There were 559 participants initially aged 70 and 519 aged 80. Compared with participants without depressive symptoms, participants with depressive symptoms had faster IADL decline during the 3 years in the 70s group, and the mean difference (95% confidence interval [CI]) was 0.11 (0.03, 0.18). However, similar association was not found in the 80s group (-0.06, 95%CI: -0.16, 0.05). Multiple group analyses showed significant differences between the age groups in the association. Conclusions: The association of depressive symptoms and IADL decline during the 3 years was different between the 70s and 80s age groups.